2018
DOI: 10.1016/j.ssci.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling causal factors of maritime incidents and accidents

Abstract: Lessons from maritime accidents are conventionally used to inform safety improvements in design and operation of ships. However, this process is only as good as the core understanding derived from accident analysis is. The current explanation of accidents is limited to direct and contributing causal factors, whereas the role of a wider socio-technical context that has given rise to causal mechanisms behind major maritime accidents in recent years is left unexplained. The paper describes analysis results of mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…This observation is in line with previous studies. For example, a study performed by Puisa et al (2018) revealed that an inadequate training was observable in numerous past accidents, and it was a frequent causal factor across all reports analyzed within aforementioned study. In addition, Graziano et al (2016) failures were associated with factors like fatigue or inadequate training/instruction.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is in line with previous studies. For example, a study performed by Puisa et al (2018) revealed that an inadequate training was observable in numerous past accidents, and it was a frequent causal factor across all reports analyzed within aforementioned study. In addition, Graziano et al (2016) failures were associated with factors like fatigue or inadequate training/instruction.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the process was augmented by a checklist, developed on the basis of previous studies (Becker & Van Eikema Hommes, 2014;Blandine, 2013). The main categories of causal factors are:  Inappropriate control input  Hardware failure  Software faulty implementation  Software faulty design  Erroneous or missing input  Inadequate control command transmission  Flawed execution due to failures in actuator or physical process  Conflicting control actions The systemic and contributory causal factors (Puisa, Lin, Bolbot, & Vassalos, 2018) have not been considered during identification of the causal factors, as the implementations of proper training for system operator and maintenance is out of the scope of system designer. The aim of the designer is to ensure the adequate reliability and availability of system functions.…”
Section: Methodsmentioning
confidence: 99%
“…The finding is further demonstrated by Rollenhagen (79) in that there is a lack of attention to the organisational context in which an accident investigation is taking place, demonstrating a lack of appreciation for Categories 2 and 3. Further evidence of a limited application of systemic causal factors in accident investigation is shown by Puisa (80,81).…”
Section: Accident Analysis and Recommendationsmentioning
confidence: 99%